Numerical investigation of the flow characteristics of Bingham fluid on a slope with corrected smooth particle hydrodynamics - Li, Yanggui; Wang, Lei; Zhao, Yun; Wang, Heping; Li, Shengshan; Jia, Jinfang (Frontiers in Environmental Science, 2022)
Bingham model can effectively describe the flow behaviour of viscoplastic fluid. It is of great significance to study the flow characteristics of Bingham fluid for understanding the dynamic mechanism of viscous debris flow. In this paper, the Bingham fluid flow on a slope is numerically researched using a corrected smooth particle hydrodynamics (CSPH) method based on periodic density re-initialization. First, the accuracy and stability of the improved SPH method is verified by the benchmark problem impacting droplet. Then, the flow characteristics of Bingham fluid on slope and the influence of slope inclination angle on Bingham fluid movement process are studied with the improved SPH method. The numerical results show that the improved SPH numerical scheme has higher accuracy and better stability, and has the ability to deal with the complex flow behaviour of unsteady Bingham fluid.